Magistrates Cum Imperio and their Temples: 396-293 BCE. - Deitrick, Ashley. (2017)
Abstract: Although temples were constructed in Rome from 396-293 BCE for a variety of reasons, the majority were built in response to victory in warfare and dedicated to a range of deities who reflected the rapid expansion of Rome's sphere of influence within Italy. Generals with imperium (the right of military command) also had the liberty to vow a temple to a chosen deity, to use revenues from the spoils of war (manubiae) for the construction of that temple, and finally to dedicate their completed work, through the process of votum, locatio, and dedicatio. The purpose of this study is to explicate the choices of deity and the location of the temples vowed by victorious generals using the narratives of Livy associated with each votum and what pattern these early Republican temples showed in the overall practice of founding temples within Rome. By doing so, this thesis will further the study of these temples, which are often overlooked in the study of Roman history, and begin a further historical and archaeological investigation of Roman generals' use of their own manubiae in temple construction.; Thesis (M.A.)--Tufts University, 2013.; Submitted to the Dept. of Classics.; Advisor: R. Bruce Hitchner.; Committee: J. Matthew Harrington, and David Proctor.; Keywords: Archaeology, and Classical studies.